PEMANFAATAN APLIKASI TIKTOK SEBAGAI MEDIA PROMOSI PRODUK KECANTIKAN WARDAH - yosi elisa lestari (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2022)
The purpose of this study was to determine the benefits of tiktok media as a communication channel and promotion media for beauty products. This study uses AIDAS theory which is used to help plan an advertisement as a whole, and the formula can be applied to a hardselling advertisement. The data of this study were obtained from informants using purposive sampling. Data collection techniques were carried out by interviewing 6 informants, participant observation and documentation.Based on the formulation of the problem contained in this study, the results of the study indicate that the use of the Tiktok application as a media for promoting wardah beauty products through Tiktok social media significantly increases sales turnover, especially during the current covid-19 pandemic. From the research that has been done, Tiktok media is one of the media that is close to millennials so that it can influence consumers to buy a beauty product from Wardah Kosmetik so that it can make an effect on increasing sales in various products, especially Wardah beauty products at the Bengkulu city outlet. Keywords: Tiktok Application, Promotional Media, Beauty Products, Wardah